Obstacles to the use of teaching methods in Saudi schools: an analytical study (The International Journal of Educational Sciences and Arts, 2024)
The current study aimed to shed light on the obstacles to using the educational area in schools in the Kingdom of Saudi Arabia. The teacher relied on modern inductive applications to review literature and previous studies and then analyze the data to reach multiple obstacles to use and teaching methods in Saudi schools. The study found that there were many obstacles mentioned from different aspects and were as follows: (Obstacles related to the administrative and leadership aspects - Obstacles on the part of teachers - Obstacles on the part of the student - Obstacles on the aspects of the educational environment - Obstacles due to technologies and equipment - Cultural and social obstacles The researcher then presented many solutions and proposals that contribute to confronting and overcoming these obstacles through the previous aspects.
Keywords: Obstacles; Teaching Methods; Teaching Strategies